Effects of selenium status, dietary glucosinolate intake and serum glutathione S‐transferase α activity on the risk of benign prostatic hyperplasia - Eichholzer, Monika; Steinbrecher, Astrid; Kaaks, Rudolf; Teucher, Birgit; Linseisen, Jakob; Rohrmann, Sabine (BJU international, 2012)
Study Type – Prognosis (case control) Level of Evidence 2 What's known on the subject? and What does the study add? Geographical and ethnic differences in the distribution of BPH and the results of migrant studies indicate that not only age, androgens and genetics, but also modifiable factors may play a role in the aetiology of BPH. Oxidative stress induced by chronic inflammation could be a cause and antioxidants, including selenoproteins, may reduce the risk. The published data related to this topic are scarce and are mainly based on cross‐sectional and case–control studies. In a nested case–control study, we observed a significant inverse association between serum selenium concentrations and the risk of BPH. These results need to be confirmed in larger, prospective epidemiological studies. Prostate enlargement is an increasing health problem as a result of an ageing population in many countries. Modifiable factors may also play a role. In the present study, before this antioxidant can be recommended as a preventive measure. OBJECTIVE • To determine whether geographical differences in the distribution of benign prostatic hyperplasia (BPH) and migrant studies indicate that modifiable factors play a role in the aetiology of BPH. Oxidative stress produced by chronic inflammation could represent one of the causes, and antioxidants, including selenoproteins, may reduce the risk. SUBJECTS AND METHODS • Conditional logistic regression was used to examine the associations of serum selenium and selenoprotein P concentrations and glutathione peroxidase activity with respect to the risk of BPH in a case–control study nested in the European Prospective Investigation into Cancer and Nutrition‐Heidelberg cohort, including 111 cases and 214 matched controls. • In addition, dietary glucosinolate intake and the serum glutathione S‐transferase α concentration was investigated. RESULTS • The risk of BPH significantly decreased with an increasing serum selenium concentration; the risk estimate was 0.83 (35% CI 0.69–0.99) per 10 µg/L increase in serum selenium concentration. • However, no significant association was present for serum selenoprotein P concentration or glutathione peroxidase activity. Risk estimates for BPH decreased with a higher intake of glucosinolates, although the results were not statistically significant. CONCLUSION • A low serum selenium concentration may increase the risk of BPH, although the findings reported in the present study need to be confirmed in larger, well‐designed epidemiological studies.